Morphometric Analysis of Suprarenal Glands (Adrenal Glands) with Multislice Computerized Tomography - Akin, Duygu; Buyukmumcu, MUSTAFA; Yilmaz, Mehmet Tugrul; Ozbek, Orhan; Ozbiner, Huseyin; Cicekcibasi, Aynur Emine; BÜYÜKMUMCU, MUSTAFA; Kabakci, Anil Didem (My University, 2017)
The aim of our study are to determine the shape, vertebrae level, height, volume, corpus medial and lateral branch thicknesses of AG and the distance from some neighboring structures on multidetector computed tomography (MDCT) images and also to determine the relationship between these data and gender, age, height, weight and body mass index (BMI). The study was conducted on a total of 420 MDCT images consisted of 220 male (mean age 63.44 +/- 8.00, 50-81 years), 200 female (mean age 61.23 +/- 7.95, 50-84 years) healthy individuals. Vertebrae level of AG (VLAG), height of AG (HAG), adrenal gland volume (VAG), corpus thickness of AG (CTAG), medial section thickness of AG (MTAG) and lateral section thickness of AG (LTAG) were investigated. In our study, RAG were observed on T12 vertebrae level in 38.19 % of males and 42.5 % of females and LAG were also observed at that level in 39.55 % of the male and 51 % of the female individuals. RAG were observed in all males and 98.5 % of the females and LAG were observed 88.63 % of the males and 94 % of the females -Y- shaped. VAG were observed lower in males compared to females in age groups and VAG was observed increasing with age in males; decreased in 60-69 age group of females and increased again in 70 and plus age group. The aim of this study is to determine normal ranges of AG sizes and the relationship of each one with sex, age, height, weight and BMI.